การผ่าตัดฝังวัสดุที่เพดานอ่อนในผู้ป่วยโรคหยุดหายใจขณะหลับจากการอุดกั้น (PALATAL IMPLANTS FOR OBSTRUCTIVE SLEEP APNEA) - โชคสวัสดิ์, กนิษฐา (วารสารมหาวิทยาลัยศรีนครินทรวิโรฒ สาขาวิทยาศาสตร์และเทคโนโลยี, 2017)
โรคหยุดหายใจขณะหลับจากการอุดกั้นเกิดจากทางเดินหายใจช่วงบนมีขนาดเล็กเกิดการยุบตัวง่าย ทำให้มีการหยุดหายใจเป็นช่วงๆ ขณะหลับ มีความเสี่ยงต่อการเกิดโรคหัวใจ หลอดเลือด โรคสมองและพฤติกรรมผิดปกติ การรักษาประกอบด้วยวิธีอนุรักษ์และวิธีผ่าตัด เมื่อการรักษาวิธีอนุรักษ์ไม่ได้ผลการผ่าตัดเป็นอีกทางเลือกของผู้ป่วย แต่การผ่าตัดหลายวิธีทำให้ผู้ป่วยปวดแผลมากและมีภาวะแทรกซ้อนหลายอย่าง การผ่าตัดด้วยวิธีฝังวัสดุที่เพดานอ่อนทำให้เพดานอ่อนตึงตัวและทางเดินหายใจยุบตัวยาก มีรายงานผลการผ่าตัดเป็นที่น่าพอใจทั้งในระยะสั้นและระยะยาวจากหลายศูนย์การรักษา การผ่าตัดนี้มีแผลผ่าตัดขนาดเล็กเมื่อเปรียบเทียบกับการผ่าตัดวิธีอื่นและสามารถนำวัสดุปลูกฝังกลับออกมาได้ผู้ป่วยไม่รู้สึกว่ามีวัสดุปลูกฝังอยู่ และไม่รบกวนการพูดการกลืน มีการนำวิธีการผ่าตัดนี้ไปใช้ร่วมผ่าตัดรักษาอย่างแพร่หลาย การผ่าตัดนี้ได้ผลในผู้ป่วยที่ได้รับการรักษาอย่างเหมาะสมและพบภาวะแทรกซ้อนจากการผ่าตัดน้อย คำสำคัญ: โรคหยุดหายใจขณะหลับจากการอุดกั้น แผลผ่าตัดขนาดเล็ก ฝังวัสดุที่เพดานอ่อน Obstructive sleep apnea (OSA) results from the combination of a structurally small upper airway and abnormal airway collapsibility. Patients with OSA develop periodic obstruction of breathing during sleep and have risks for cardiovascular and neurobehavioral diseases. The treatment options include medical and surgical modalities, when medical fails, surgical option is the alternative. However, many surgical procedures for OSA cause serious postoperative pain and complications. The palatal implants induce the stiffening of the soft palate and increase the upper airway stability. Successful results in the treatment of OSA have been reported in the short-term and long-term in many centers. The procedure is not as invasive as some of the other surgical procedures and reversible. Patients can neither see or feel the implants, nor do they interfere with swallowing or speech. This has been widely adopted and performed in conjunct with other procedures. Palatal implants in the treatment of OSA result in success in carefully selected patients without serious complications. Keywords: Obstructive Sleep Apnea, Minimally Invasive Surgery, Palatal Implants